Dentists' Attitudes in Jordan towards the Shortened Dental Arch Concept: A Cross-Sectional Study - Abu-Awwad, Motasum (Int J Dent, 2019)
AIMS: To assess the awareness, knowledge, attitudes, and application of the shortened dental arch (SDA) concept by dentists in Jordan. MATERIALS AND METHODS: In this cross-sectional survey, a questionnaire was disseminated to a random sample of 150 dentists working in private practices, university hospitals, or governmental institutes. The chi-square (X(2)) test was used to examine associations. RESULTS: One hundred and six dentists responded (70.7% response rate). Fifty-five were females. 82.1% were aware of the SDA concept. The fewer the years of experience, the more likely the dentists were aware of the SDA concept (X(2), P=0.024) and the more likely they learned about it through undergraduate education (X(2), P < 0.001). In a hypothetical clinical situation of a patient >50 years of age with missing molar teeth, 45.3% agreed that the molars should be replaced, while 54.7% did not agree. Improving mastication was the main reason for agreeing (81.6%), while having reduced functional benefit was the main reason for disagreeing (64.9%). The treatment modality most commonly recommended was implants fixed partial dentures (84.9%). Of those aware of SDA, 67.8% agreed it could have a useful place in treatment planning within Jordan. Cost reduction for patients was the main reason for this answer, as reported by 51% of those who agreed. 26.4% did not apply SDA for any of their patients, while 50.6% applied it for <10% of their patients. CONCLUSION: The majority of the dentists was aware of the SDA concept and had a positive attitude towards it; however, few of them applied it in their practice.